Religious Coping in Parents of Children with Down Syndrome: A Systematic Review of the Literature - Çaksen, Hüseyin (Journal of religion and health, 2025)
Having a child with Down syndrome (DS) is stressful for families. Social, physical, economic and emotional difficulties are the most challenging stressors for parents of children with DS. Therefore, parents who have children with DS have used various types of coping strategies. This systematic review investigates religious coping in parents of children with DS to synthesize what is known of the literature regarding religious coping among parents of children with DS. Pubmed and Scopus databases were searched with no restriction on language and the year of publication. Additionally, manual searches of the retrieved articles’ references were performed. Forty-four original studies published between 2000 and 2023 were included in the review. No study on the subject was found in either Pubmed or Scopus before 2000. Most studies were conducted in USA 7 (15.9%), Egypt 7 (15.9%), and Türkiye 6 (13.6%). In the studies, the total number of participants was 4266, range between 8 and 530 (median 55.5). The ethnic origins of the participants were very diverse and the studies included participants from many cultures around the world. Based on the studies, we identified seven themes that represented the main stressors encountered by parents/caregivers of children with DS: "information deficits," "child caregiving burdens," "familial difficulties," "financial difficulties," "challenges related to social and professional support," "society’s misconceptions," and "worries about the future." The most commonly (n = 12, [27.2%]) used coping scale was coping orientation to problems experienced. Religious coping was the coping strategy most frequently used by participants in 36 (81.8%) studies. Religion, spirituality, and belief in Allah (God) were of central importance for most participants in most of the studies. Most parents reported that belief in Allah (God) encouraged them to accept the diagnosis of DS and feel better and become stronger; provided improvements in the lives of families and the necessary resources to face their difficulties; played a fundamental role in adaptation with the conditions of their children with DS; brought them peace of mind and a sense of hope; and motivated them to keep on moving forward. In conclusion, religion plays an important role in the lives of most parents of children with DS. Religious coping has been used by parents of children with DS in many cultures around the world, regardless of religion, race, or ethnicity. Belief in Allah (God), belief in fate and belief in the afterlife, provided physical, mental and psychosocial relief for most parents of children with DS.